The changing world of work and employment relations: a multi-level institutional perspective of the future. (2nd January 2018) - Lansbury, Russell D.
ABSTRACT: The social and economic relevance of work and employment relations is as great today as it has been in the past and is likely to be of even greater importance in the future. Yet, as a field of academic study, traditional approaches to work and employment relations face a number of challenges, particularly in an era of globalization. Understanding the changing nature of work and employment relations has significant implications for economic prosperity and social harmony in all societies. How workers engage in new forms of employment, such as the 'shared economy', and exercise influence over their employment conditions are challenges which face not only employers but also governments and society at large. As the world of work becomes increasingly affected by global as well as local factors, a multi-level perspective is needed which takes into account the interaction between national, sectoral and transnational spheres of work and employment relations.